Book Review: People skills for library managers: A common sense guide for beginners - Ida Farida (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2004)
Judul Buku: People skills for library managers: A common sense guide for beginners Pengarang: Lucile Wilson Tempat Terbit: Colorado, as Penerbit: Libraries Unlimited, inc Tahun Terbit: 1996 Oleh: Ida Farida, MLIS